IMPROVING THE ABILITY OF WRITING PANTUN USING THE MIND MAPPING METHOD IN CLASS VIII STUDENTS OF SMP NEGERI 2 PEGANTENAN FOR ACADEMIC YEAR 2020/2021 - Fredy Yunanto (Universitas Pahlawan Tuanku Tambusai, 2022)
The Mind Mapping method is a creative way for each student to generate ideas, record what is learned, or plan new assignments. Based on this background, the researchers are interested in taking the title